The role of FilGAP, a Rac‐specific Rho‐GTPase‐activating protein, in tumor progression and behavior of astrocytomas - Hara, Atsuko (Cancer Med, 2016)
FilGAP, a Rac‐specific Rho‐GTPase‐activating protein (GAP), acts as a mediator of Rho/ROCK‐dependent amoeboid movement, and its knockdown results in Rac‐driven mesenchymal morphology. Herein, we focused on the possible roles of FilGAP expression in astrocytomas. In clinical samples, FilGAP expression was significantly increased in grade (G) II astrocytomas as compared to normal astrocytes, but its expression strongly decreased in a grade‐dependent manner, and was positively associated with isocitrate dehydrogenase 1 (IDH1) mutations and inversely to cytoplasmic Rac1. Patients with astrocytoma showing a high FilGAP score had favorable overall survival as compared to the low score patients. Multivariate Cox regression analysis also showed that a high FilGAP score was a significant and independent favorable prognostic factor. Moreover, patients with high FilGAP score and IDH1 mutant‐type astrocytomas had significantly the best Overall survival (OS) and Progression‐free survival (PFS), in contrast to the patients with low FilGAP score and wild‐type IDH1 tumors who had the worst prognosis. In GIV tumors (GBM: glioblastomas), elongated tumor cells with low FilGAP expression were frequently observed in tumor core lesions, whereas the rounded cells with abundant expression were found in the peripheral areas adjacent to non‐neoplastic brain tissues. In an astrocytoma cell line, suppression of endogenous FilGAP expression by siRNAs caused an increased proportion of mesenchymal elongated cells, probably through increased Rac1 activity. These findings suggest that FilGAP, as well as IDH1 status, may be useful for predicting the behavior of astrocytomas. In addition, the FilGAP/Rac1 axis may serve as an important regulator of tumor progression in GBMs, probably through alteration of cell morphology.